Rasa berguna bertindak sebagai mediator dalam perhubungan antara kaedah penugasan latihan dengan motivasi latihan - Suriani, Mat Ali (Universiti Malaysia Sarawak, UNIMAS, 2007)
This study was conducted to examine whether employees’ perceived importance of the training program would be one variable that mediate the relationship between training assignment and training motivation. Data for this study was collected through in-depth interview and survey questionnaires.Outcomes of testing mediating model using stepwise regression analysis showed that the inclusion of perceived importance into analysis had increased effect of training assignment on training motivation. This result confirms that perceived importance does act as a full mediator in training assignment of Dewan Bandaraya Kuching Utara, Sarawak. In addition, implications of this study to training practices and theory, methodological and conceptual limitations, as well as direction for future research are discussed.